PEMBINGKAIAN BERITA ISU PELEMAHAN RUPIAH MENJELANG PEMILIHAN PRESIDEN 2019 PADA MEDIA ONLINE - Marcella Apriani (Jurnal Dakwah Tabligh, 2019)
The study entitled "Framing of the News Issue of Weakening the Rupiah Ahead of Presidential Election 2019 in Media Online" aims to find out how online media news frames the issue of weakening the rupiah ahead of the presidential election. The news in this study is news that has a high popularity on the issue of the rupiah, namely the period 2 September-8 September 2018. Based on that period, four news were found through the google database. The method in this study is descriptive qualitative research method using the theory of framing analysis of Zhongdang Pan and Gerald M Kosicki. By using four structures from Pan and Kosicki namely syntactic, script, thematic, and rhetorical structures. The results of this study indicate that Kompas.com's online media news framed the news of rupiah depreciation in the political frame, it is seen the use of the word "frying" in quoting statements to describe the rise of the US dollar against the rupiah exchange rate.